2016
DOI: 10.2471/blt.16.174441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ebola virus disease preparedness in the WHO South-East Asia Region

Abstract: ObjectiveTo conduct assessments of Ebola virus disease preparedness in countries of the World Health Organization (WHO) South-East Asia Region.MethodsNine of 11 countries in the region agreed to be assessed. During February to November 2015 a joint team from WHO and ministries of health conducted 4–5 day missions to Bangladesh, Bhutan, Indonesia, Maldives, Myanmar, Nepal, Sri Lanka, Thailand and Timor-Leste. We collected information through guided discussions with senior technical leaders and visits to hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…However, the risk of in-flight transmission of influenza appears to be higher than that of SARS-CoV-2. The transmission rate (secondary attack rate) in our study was 3.69% while secondary attack rate for influenza in in-flight passengers ranged between 4.3% and 7.5% based on most reports [26,27].…”
Section: Discussionmentioning
confidence: 49%
“…However, the risk of in-flight transmission of influenza appears to be higher than that of SARS-CoV-2. The transmission rate (secondary attack rate) in our study was 3.69% while secondary attack rate for influenza in in-flight passengers ranged between 4.3% and 7.5% based on most reports [26,27].…”
Section: Discussionmentioning
confidence: 49%
“… 10 A WHO assessment on Ebola virus preparedness in WHO Southeast Asia region showed that multilevel and multisectoral collaboration and coordination structures were most advanced aspects in preparedness, as a result from pandemic preparedness. 11 Van Beneden et al 12 also describes US Centers for Disease Control and Prevention outreach to clinicians, including assisting clinicians managing patients with Ebola, sharing updated information with the clinical community, and coordinating information sharing among clinicians managing patients with Ebola in the United States and Europe. We conclude that the multisectoral approach for EVD preparedness has been experienced widely.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, all countries assessed by data from the annual reporting self-reported the existence of IHR multisectoral committees, but the mission found multisectoral committees in only 25% of these countries. This finding provided evidence that the self-reporting of IHR capacities might not accurately reflect the actual capacities in some countries ( 8 , 9 ).…”
Section: Who Joint External Evaluation Toolmentioning
confidence: 97%